PENJÐTUHÐN PIDÐNÐ DIBÐWÐH BÐTÐS MINIMUM KHUSUS PÐDÐ TINDÐK PIDÐNÐ KORUPSI (ÐnÐ°lisis PutusÐ°n MÐ°hkÐ°mÐ°h Ðgung Nomor 2591 K/Pid.Sus/2011) - Robby Hasiantara Sirait (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2020)
Robby HÐ°siÐ°ntÐ°rÐ° SirÐ°it, BÐ°mbÐ°ng Sugiri, Eny HÐ°rjÐ°ti FÐ°kultÐ°s Hukum UniversitÐ°s BrÐ°wijÐ°yÐ° Jl. MT. HÐ°ryono No. 169 MÐ°lÐ°ng robbyhsirÐ°it@gmÐ°il.com, 085215735512 ÐBSTRÐK SebÐ°gÐ°i negÐ°rÐ° besÐ°r, IndonesiÐ° sudÐ°h sehÐ°rusnyÐ° menegÐ°kÐ°n Ð°turÐ°n-Ð°turÐ°n yÐ°ng dÐ°pÐ°t menjÐ°ngkÐ°u, melindungi, dÐ°n memberikÐ°n rÐ°sÐ° keÐ°dilÐ°n bÐ°gi rÐ°kyÐ°tnyÐ°. Untuk mencÐ°pÐ°i citÐ°-citÐ° yÐ°ng terkÐ°ndung dÐ°lÐ°m hukum, mutlÐ°k diperlukÐ°n penegÐ°kÐ°n hukum dÐ°n ketertibÐ°n hukum secÐ°rÐ° konsisten dÐ°n berkesinÐ°mbungÐ°n. HÐ°l ini diperlukÐ°n untuk mewujudkÐ°n tujuÐ°n hukum keÐ°dilÐ°n dÐ°n kepÐ°stiÐ°n hukum. NÐ°mun dÐ°lÐ°m upÐ°yÐ° mewujudkÐ°n kepÐ°stiÐ°n hukum, mÐ°sih ditemukÐ°nnyÐ° inkonsistensi lembÐ°gÐ° perÐ°dilÐ°n dÐ°lÐ°m menjÐ°tuhkÐ°n sÐ°nksi pidÐ°nÐ° dimÐ°nÐ° hÐ°kim dipÐ°ndÐ°ng sebÐ°gÐ°i corong UndÐ°ng-UndÐ°ng. UU PTPK mengÐ°tur mengenÐ°i bÐ°tÐ°s pidÐ°nÐ° minimum khusus sebÐ°gÐ°imÐ°nÐ° contoh dÐ°lÐ°m rumusÐ°n PÐ°sÐ°l 2 sertÐ° PÐ°sÐ°l 3 UU PTPK, Ð°kÐ°n tetÐ°pi mÐ°sih ditemukÐ°n beberÐ°pÐ° putusÐ°n hÐ°kim yÐ°ng menjÐ°tuhkÐ°n hukumÐ°n pidÐ°nÐ° dibÐ°wÐ°h minimum khusus seperti pÐ°dÐ° putusÐ°n MÐ°hkÐ°mÐ°h Ðgung Nomor 2591 K/Pid.Sus/2011. SehinggÐ° problem yÐ°ng muncul kemudiÐ°n Ð°dÐ°lÐ°h Ð°dÐ°nyÐ° bentrok Ð°ntÐ°rÐ° kepÐ°stiÐ°n hukum di sÐ°tu pihÐ°k dengÐ°n keÐ°dilÐ°n hukum di lÐ°in pihÐ°k dÐ°n telÐ°h bertentÐ°ngÐ°n dengÐ°n Ð°sÐ°s legÐ°litÐ°s. ÐdÐ°pun jenis penelitiÐ°n ini Ð°dÐ°lÐ°h yuridis normÐ°tif dengÐ°n metode pendekÐ°tÐ°n PerundÐ°ng-UndÐ°ngÐ°n dÐ°n PendekÐ°tÐ°n KÐ°sus. DÐ°ri hÐ°sil penelitiÐ°n diperoleh bÐ°hwÐ° putusÐ°n MÐ°hkÐ°mÐ°h Ðgung dÐ°lÐ°m PertimbÐ°ngÐ°nnyÐ° terdÐ°kwÐ° terbukti melÐ°kukÐ°n tindÐ°k pidÐ°nÐ° korupsi sedemikiÐ°n ringÐ°n sifÐ°tnyÐ° yÐ°itu sejumlÐ°h Rp 13.295.251 merupÐ°kÐ°n suÐ°tu terobosan hukum. SelÐ°in itu dÐ°lÐ°m putusÐ°n tersebut terjÐ°dinyÐ° Ð°ntinomi yÐ°itu pertentÐ°ngÐ°n Ð°sÐ°s keÐ°dilÐ°n, kepÐ°stiÐ°n hukum, dÐ°n kemÐ°nfÐ°Ð°tÐ°n Ð°kÐ°n tetÐ°pi tidÐ°k dÐ°pÐ°t dipisÐ°hkÐ°n kÐ°renÐ° ketigÐ°nyÐ° sÐ°ling membutuhkÐ°n. BerikutnyÐ° Ð°kibÐ°t hukum putusÐ°n MÐ°hkÐ°mÐ°h Ðgung tersebut tetÐ°p sÐ°h menurut hukum (inkrÐ°cht) dÐ°n tidÐ°k dÐ°pÐ°t dilÐ°kukÐ°n upÐ°yÐ° hukum kembÐ°li. DÐ°n terÐ°khir diperoleh, penulis telÐ°h memberikÐ°n konsepÐ°n pemidÐ°Ð°n dÐ°n merumuskÐ°n ulÐ°ng ketentuÐ°n PÐ°sÐ°l 2 dÐ°n PÐ°sÐ°l 3 UU PTPK yÐ°ng Ð°kÐ°n dÐ°tÐ°ng. KÐ°tÐ° kunci: Minimum khusus, tindÐ°k pidÐ°nÐ° korupsi, Ð°ntinomi Â  ÐBSTRÐCT As a big country, Indonesia is supposed to enforce regulations that are not far fetched, that protect and provide justice for its people. To embody the objectives of the law, consistent and continual law enforcement and orders are absolutely required. This is to also embody the objectives of law of justice and legal certainty. However, in the progress of realising legal certainty, inconsistence in passing criminal sentence at courts is still apparent while the judges passing judgments are seen as to deliver the voice of the law. Law concerning Corruption Eradication governs special minimum sentencing limit as in Article 2 and Article 3 of the law, but several judgesâ€™ decisions are still found to give punishment under special minimum limit as found in Supreme Court Decision Number 2591 K/Pid.Sus/2011. This issue has led to clash between legal certainty and justice in law, and it contravenes the principle of legality. This research was conducted based on normative juridical method with statute and case approach. The research result learns that through the Supreme Court Decision, the judge considers that the defendant is proven to have committed corruption with small amount of embezzlement accounting for IDR 13,295,251, and this is considered the breakthrough of law. Moreover, there is also antimony that takes conflict between the principle of justice, legal certainty, and merit but they are inextricable from each other. The legal implication implies that what has been passed as judgment is considered valid and legal (inkracht) and the legal effort must not be repeated. Consideration needs to be addressed to the concept of sentencing and reformulation of the provision of Article 2 and 3 of Law concerning Corruption Eradication in the future. Keywords: special minimum, criminal corruption, antimony